Fundamentals of business ethics : a developing country perspective - Elegido, J. M. (Ibadan : Spectrum Books, 1996)
Covers main issues that arise in the field of business ethics both at the corporate level and at the level of the individual manager.
Includes bibliographical references (p. [397]-409) and index
oif 13/03/15
Loan
Keywords: Business ethics -- Developing countries; Business ethics. &#x000A